2019
DOI: 10.1152/japplphysiol.00794.2018
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic abnormalities during muscle metaboreflex activation in patients with type 2 diabetes mellitus

Abstract: Metaboreflex is a reflex triggered during exercise or postexercise muscle ischemia (PEMI) by metaboreceptor stimulation. Typical features of metaboreflex are increased cardiac output (CO) and blood pressure. Patients suffering from metabolic syndrome display hemodynamic abnormalities, with an exaggerated systemic vascular resistance (SVR) and reduced CO response during PEMI-induced metaboreflex. Whether patients with type 2 diabetes mellitus (DM2) have similar hemodynamic abnormalities is unknown. Here we cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…It is then not surprising that differently from what has been found in T1DM, T2DM, and insulin resistance have been often associated with an increase in sympathetic tone [104]. This may explain why these subjects often experience elevated blood pressure and exaggerated increments in SVR in response to effort [105,106]. Moreover, cerebral auto-regulation has been found impaired in these patients [106].…”
Section: Cardiovascular Dysregulation In T2dmmentioning
confidence: 95%
“…It is then not surprising that differently from what has been found in T1DM, T2DM, and insulin resistance have been often associated with an increase in sympathetic tone [104]. This may explain why these subjects often experience elevated blood pressure and exaggerated increments in SVR in response to effort [105,106]. Moreover, cerebral auto-regulation has been found impaired in these patients [106].…”
Section: Cardiovascular Dysregulation In T2dmmentioning
confidence: 95%
“…Contradictory results observed in animal models have also been reported in patients with diabetes, where the picture is complicated by the large interindividual variability of the methods used to assess infarct size, so that a large number of patients is necessary to define the efficacy of new cardioprotective approaches in humans (Reinstadler et al, 2017). Moreover, in the clinical scenario, IPC is not so feasible to investigate.…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…We can speculate that the inefficacy of RIC in diabetes may also be in part explained by the autonomic dysfunction that is getting worse in type 2 diabetes mellitus patients (Istenes et al, 2014). Indeed, the metaboreflex (the reflex response stimulated by metabolite accumulation during limb exercise and/or ischaemia) is abnormal in type 2 diabetes mellitus patients and it is characterised by an exaggerated vasoconstriction (perhaps due to sympathetic overstimulation) not accompanied by a concomitant increase in heart performance (Roberto et al, 2019). This speculation is in line with a study, where the plasma dialysate collected from patients with diabetes after RIC triggered cardioprotection only in the absence of diabetic neuropathy of the upper limbs (Jensen, Støttrup, Kristiansen, & Bøtker, 2012).…”
Section: Effects Of Hyperglycaemia and Diabetes On Remote Ischaemic Cmentioning
confidence: 99%
“…Interestingly, the magnitude of MSNA response to PEI was positively correlated with metabolic markers of disease severity (glucose, HbA1c, and HOMA-IR), which suggests that the severity of disease has significant impact on the enhanced expression of the exercise pressor reflex in T2D. In this regard, a recent study (Roberto et al, 2019) that reported a normal BP response to PEI following rhythmic handgrip exercise (30% MVC) had a cohort of T2D patients with relatively wellcontrolled blood glucose (106.41 ± 11.2 mg/dl; HbA1c 7.05 ± 0.10%). Although it is possible that the lower-intensity rhythmic exercise did not produce sufficient metabolic stimuli to unmask a difference in metaboreflex-induced BP responses between groups, notably T2D patients in this study exhibited exaggerated vasoconstriction during PEI.…”
Section: Neurovascular Dysregulation During Exercise In Type 2 Diabetesmentioning
confidence: 97%
“…Indeed, T2D rats exhibit augmented BP responses to isolated mechanical stimuli (i.e., tendon stretch), suggesting an augmented mechanoreflex . Furthermore, studies in humans suggest T2D also augments the metaboreflex (Holwerda et al, 2016a;Roberto et al, 2019). Specifically, Holwerda et al (2016a) showed exaggerated MSNA and BP responses to postexercise ischemia (PEI) following isometric handgrip exercise (30 and 40% maximal voluntary contraction: MVC; Figure 1).…”
Section: Neurovascular Dysregulation During Exercise In Type 2 Diabetesmentioning
confidence: 99%